The Newcomer - Adeleke, Dapo (Literamed Publications Ltd, 2005)
Babatunde Santos Ronaldo's admission to the university sets the pace for a quest to use the instrument of law in redressing the injustice and oppression against his people. But instead of law, an inconsiderate admissions registrar forces Babatunde to study English and Literature. Musa becomes his good genius, spurring him to a greater height of creative writing, while Rabi provides the romantic angle in a story that reminds one of the recurrent issue of unity in diversity among the Nigerian populace.
Keywords: Fiction